Strategi Pengembangan Destinasi Wisata Kawasan Segitiga Emas Trenggalek Berbasis Daya Dukung Kawasan - Mochamad Firhan Vallerian; Ulul Hidayah (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2024)
Sustainable tourism must be developed in line with land-carrying capacity and urban land-use plans. Adopting the Trenggalek Golden Triangle (TGT) - an area of high tourism potential -this research is designed first to determine land carrying capacity, second to cross-reference the relevance of TGT’s location with land development classes, and third, to propose prioritized zones for tourist development. This research utilizes Geographic Information System (GIS) Technology with Land Capability Unit Analysis (SKL) and IDW Interpolation Analysis. SKL data involves nine parameters: morphology, ease of work, slope stability, foundation stability, water availability, drainage, resistance to erosion, waste disposal, and risk of natural disasters. This study classifies TGT’s area into three classes in terms of land capability: low, medium, and relatively high. This study finds that areas with relatively high land capacity are suitable for tourism development. However, they are all located in disaster-prone areas. Thus, a sustainable tourism destination development strategy is required. Based on SKL and IDW analysis, it is found that Munjungan District is configured as a tourist destination with a priority development strategy. At the same time, Kampak and Watulimo Districts are classified as areas with an advanced development strategy. Strategies for tourist destinations with priority development include providing tourism-related infrastructure, management, culinary facilities, lodging facilities, public education, and sustainable promotion. Strategies for tourist destinations with advanced development involve the provision of sustainable infrastructure, promotion, environmental conservation, and education.Keyword: regional carrying capacity; strategy; Trenggalek; tourism AbstrakPariwisata berkelanjutan harus dibangun seiring dengan daya dukung lahan dan rencana pemanfaatan lahan kota. Dengan mengadopsi Kawasan Segitiga Emas Trenggalek - zona yang memiliki potensi pariwisata tinggi – sebagai studi kasusnya, penelitian ini didesain untuk: pertama mengetahui kemampuan lahan; kedua menstudi kesesuaian lokasi wisata dengan kelas pengembangan lahan; dan ketiga menemukan zona prioritas pengembangan wisata. Penelitian ini memanfaatkan Teknologi Sistem Informasi Geografis (SIG) dengan Analisis Satuan Kemampuan Lahan (SKL) dan Analisis IDW Interpolation. Data SKL melibatkan sembilan parameter seperti morfologi, kemudahan dikerjakan, kestabilan lereng, kestabilan pondasi, ketersediaan air, drainase, ketahanan terhadap erosi, pembuangan limbah, dan risiko bencana alam. Hasil analisis mengklasifikasikan kawasan menjadi tiga kelas kemampuan lahan, yaitu: rendah, sedang, dan agak tinggi. Meskipun kawasan dengan kemampuan lahan agak tinggi cocok untuk pengembangan pariwisata, hampir semua lokasi pariwisata dengan kategori ini berada di kawasan rawan bencana. Sehingga, strategi pengembangan destinasi pariwisata yang berkelanjutan diperlukan. Berdasarkan analisis SKL dan IDW Interpolation, ditemukan jika Kecamatan Munjungan diidentifikasi sebagai destinasi wisata dengan strategi pengembangan prioritas, sementara Kecamatan Kampak dan Watulimo sebagai destinasi wisata dengan strategi pengembangan lanjutan. Strategi pengembangan wisata prioritas mencakup pengadaan infrastruktur, manajemen wisata, kulinari, fasilitas penginapan, edukasi masyarakat, dan kegiatan promosi yang berkelanjutan. Strategi untuk kategori lanjutan melingkup pembangunan berkelanjutan di bidang infrastruktur, promosi, konservasi lingkungan, dan edukasi.Kata kunci: daya dukung kawasan; strategi; Trenggalek; wisata